Persepsi Konsumen Muslim tentang LGBT yang Mempengaruhi Pembelian Produk Dalam Intervensi Religiusitas - Laila Alfi; Marliyah Marliyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study examines how the perceptions of Muslim consumers in Indonesia regarding the phenomenon of companies that support LGBT as an effort to intervene in community religiosity. Descriptive research is research used by researchers in this study. Researchers describe facts, data, and information obtained from literature studies such as books, and journals to research results related to the research topic. In this study, it is explained that there are several impacts or effects felt by a company if it openly or openly provides support to LGBT actors in Indonesia. Among them is the decrease in the number of Muslim consumers, and the decrease in their income which greatly affect the image of a company. This phenomenon is based on facts in the field that have occurred in large companies such as Gojek and Starbucks in Indonesia. As a country where the majority of the population is Muslim, the Indonesian people are very concerned about matters relating to religious principles. So that this phenomenon that occurs can be said to be part of the intervention of community religiosity towards a product and company Keywords: Perception, Muslim Consumers, LGBT, Religiosity